Solar Radiation in Architectural Projects as a Key Design Factor for the Well-Being of Persons with Alzheimer’s Disease - Jose-Manuel Almodóvar-Melendo; Santiago Quesada-García; Pablo Valero-Flores; Joseph Cabeza-Lainez (Buildings, 2022)
The beneficial effects of solar radiation on human health are well documented. One necessary mechanism triggers the production of vitamin D, whose insufficiency has been linked to a variety of disorders such as diabetes; hypertension; and, more recently, amyloidosis and Alzheimer’s disease. However, there are few architectural designs capable of ensuring the adequate provision of solar radiation inside buildings. Conventional fenestration is not sufficient to provide for significant doses of sunlight, even to prevent seasonal affective disorder (SAD). In this paper, we discuss the effect of new design alternatives for skylights, especially in the refurbishment of obsolete facilities. Based on the authors’ previous studies, we defined a theoretical model that was subsequently adapted to a real building that was to be retrofitted in an area near Sevilla. After such complex refurbishment was executed, we analyzed the performance of buildings in warm and sunny climates, as is the case of southern Spain, where cloudiness is very scarce and available simulation models are not useful. The study of the factors that relate to sunlight; UV reception and energy; and, to a certain extent, other aspects such as ventilation and insulation has been considered a priority. Many architectural designs are presented as correct if the thermal requirements alone are met, even at the risk of later energy waste in lighting devices and visual or physical discomfort. On the other hand, large glazed areas allow for more daylight and UV radiation into a space if properly treated, but they may also produce excessive heat gains or losses, which increase the air-conditioning cooling or heating load, respectively. The uncontrolled increase in temperature can have negative effects on the well-being of a person with Alzheimer’s dementia. To avoid these problems, we have considered the combined effect of daylight and energy from the beginning of the skylight design-process. Daylighting software, based on configuration factors that we have applied in studies of the complex problem of there being direct sunlight over architectural structures, has been used. This question cannot be treated adequately with conventional programs for overcast skies. The skylights have already been constructed, with special UV increasing glazing and on-site measurements in the offices to complement the computer simulation data. The results show that it is possible to achieve energy saving and high radiation levels in winter without increasing heat loads during the summer. Ventilation is also improved through the aerodynamic design of the clerestories. All this is considered beneficial to improve the condition of users with cognitive diseases as Alzheimer’s disease, by virtue of adapted spaces.